2024
DOI: 10.1080/22221751.2024.2315964
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly conserved Trypanosoma cruzi antigens for the development of a universal serological diagnostic assay

Alicia Majeau,
Eric Dumonteil,
Claudia Herrera

Abstract: Chagas Disease is an important neglected tropical disease caused by Trypanosoma cruzi . There is no gold standard for diagnosis and commercial serological tests perform poorly in certain locations. By aligning T. cruzi genomes covering parasite genetic and geographic diversity, we identified highly conserved proteins that could serve as universal antigens for improved diagnosis. Their antigenicity was tested in high-density peptide microarrays using well-characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Despite the differences, the overall performance is comparable, especially among the commercial kits, which are still available to this date. Moreover, DTU genetic diversity may not be responsible for disagreements between serological tests, and rather may be more to individual variation in antibodies’ profiles ( Majeau et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences, the overall performance is comparable, especially among the commercial kits, which are still available to this date. Moreover, DTU genetic diversity may not be responsible for disagreements between serological tests, and rather may be more to individual variation in antibodies’ profiles ( Majeau et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…511633.79)(Ibañez et al 1988), showed 76% sensitivity in 61 samples of infected sera(Mucci et al 2017). It is therefore conserved in a majority of strains of T. cruzi and can perhaps be used universally where Chagas' disease testing is necessary(Negrette et al 2008;Majeau et al 2024). 6% identical, and IFN-γ was 17.9% identical.…”
mentioning
confidence: 99%